"That rare gift: perfect hands on a horse": Radclyffe Hall's eros of cross-species communion. Issue 1 (2nd January 2020) - D'Stair, Sarah
ABSTRACT: Scholars of Radclyffe Hall's fiction have focused primarily on her advocacy for human gender and sexual freedom; however, closer attention to human-animal connections in her work reveals concern for equity across species lines as well. The Well of Loneliness (1928) in many ways challenges the human-animal binary just as powerfully as it does gender and sexual binaries. By narrating multi-species relationships marked by kinetic body play, the novel suggests that eroticism can be a harmonizing force that traverses deeply-ingrained social boundaries between animals of all kinds. By examining the protagonist's interactions with her animal friends, I argue that Hall's text privileges intimate, unspoken gestures of body and voice over the more confining structures of human language. Hall also implements grammatical constructs in animal scenes that open possibilities for co-forming, co-shaping interrelationality, a narrative move that acknowledges and appreciates, rather than ignores, radical alterity between species. Ultimately, I argue, Hall envisions a rehabilitative ecological vision for human and nonhuman animals, writing all creatures as co-constitutive actors within the intimate spaces they share.